THE CUSTOMER PERCEPTION OF BRIGHT AUTO PLAST PVT LTD - Divyaranjani R (International Journal of Supply Chain Management, 2018)
To study the customer perception of Bright Auto Plast Pvt Ltd." This study is confined to the automobile companies only. The sample size is chosen as 30. Convenience Sampling is used, and descriptive research is adopted. This study is mainly carried on to find the customer satisfaction level of Bright Auto Plast Pvt Ltd. The major factors that lead to customer satisfaction are the product, pricing, quality, and service. The study has found that the existing system in Bright Auto Plast is not adequate and can be modified accordingly to make it effective.